Karakteristik Ekstrak Pewarna Daun Singkong (Manihot esculenta C.) Pada Perlakuan Intensitas Cahaya Selama Penyimpanan - Elsa, Erina Novandri; Wartini, Ni Made; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 11 No 1 (2023): Maret, 2023)
The chlorophyll content of cassava leaf extract is sensitive to light, heat, oxygen, and chemical degradation. The aims of this study were (1) to determine the characteristics of the cassava leaf dye extract in the light intensity treatment during storage and (2) to determine the light intensity that could give the smallest decrease in the cassava leaf dye extract during storage. This study used a simple completely randomized design with light intensity treatment consisting of 5 levels, namely 1800 lumens, 2600 lumens, 3800 lumens, 4500 lumens, and 5200 lumens. Each treatment was carried out 3 times so that there were 15 experimental units. The results showed that the light intensity treatment had an effect on decreasing the levels of total chlorophyll, chlorophyll a, chlorophyll b, antioxidant capacity, brightness (L*), redness (a*), and yellowness (b*) of cassava leaf extract during storage. Light intensity 1800 lumen was the treatment that gave the smallest decrease in cassava leaf extract with a percentage change in total chlorophyll content of 28.10%, chlorophyll a 22.68%, chlorophyll b 31.44%, antioxidant capacity 27.67%, the level of redness (a*) was 65.82%, but caused an increase in the value of the brightness level (L*) of 44.79%, and the level of yellowness (b*) of 57.14% for 7 days of storage.